The impact of celebrity-following activities on endorsement effectiveness on microblogging platforms: A parasocial interaction perspective. Issue 2 (5th June 2017) - Ding, Yue; Qiu, Lingyun
Abstract : Purpose: Celebrity endorsement on microblogging platforms (such as Twitter or Weibo) has become a widely adopted marketing practice. Compared to its counterpart on traditional mass media, celebrity endorsement on microblogging platforms has some unique characteristics. For example, the endorsement information is usually more implicit and the endorsers tend to use different tactics so as to maximize the impact on their followers. However, these new practices have not been thoroughly investigated and the underlying mechanism by which the endorsers influence potential information receivers is not well understood. Anchored on the theory of parasocial interaction borrowed from the mass communication literature, this paper aims to reveal the underlying mechanism of celebrity endorsement on microblogging platforms. More specifically, it examines the relationship between the intensity of microbloggers' various celebrity-following activities and endorsement effectiveness. Design/methodology/approach: The authors designed and conducted a Web-based survey containing scales for all focal constructs and demographic and control variables. Through online and offline campus advertisement, undergraduate and graduates students who have used microblogging for at least three months were recruited. Findings: First of all, the survey results show that the intensity of users' celebrity-following activities on microblogging platforms has a positive effect on the effectiveness of celebrity endorsement. Second, the positive effect of the intensity of microbloggers' celebrity-following activities on the effectiveness of celebrity endorsement is mediated by the perceived parasocial interaction with the endorsers. Research limitations/implications: Firstly, most respondents of the survey are university students. Second, because of the intrinsic disadvantage of the survey method, the causal relationship between constructs cannot be examined directly. Last, parasocial interaction/relationship is a complex theoretical construct whose influence is unveiled partially in this research. Practical implications: First, this study found that the effectiveness of celebrity endorsement on microblogging platforms are largely affected by celebrity-followers' online involvement. Second, this study revealed that celebrity-following activities that help enhance followers' perceptions of parasocial interactions are particularly beneficial for endorsement effectiveness. Last, the exploratory analysis further revealed that followers' perceptions of ingenuousness and companionship are two key sub-dimensions of parasocial interaction. Originality/value: First, the authors verified the positive relationship between information receiver's involvement and the effectiveness of celebrity endorsement in the context of microblogging platforms. Second, this study found that parasocial interaction fully mediates the relationship between celebrity-following intensity and endorsement effectiveness. Last, through an exploratory factor analysis, the authors further decomposed the construct of parasocial interaction into three sub-dimensions, namely, ingenuousness, empathy and companionship.